2020
DOI: 10.4103/ajns.ajns_284_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative outcome analysis of enterprise and neuroform stent-assisted coiling of cerebral aneurysms: A review of the literature

Abstract: Introduction: One of the popular treatment strategies for complex cerebral aneurysms with wide necks or low dome-to-neck ratios is stent-assisted coiling. The most widely used intracranial stents for stent-assisted coiling are Neuroform (NF) and Enterprise (EP) stents. The purposes of this study are to review the recent literature of the past 5 years to compare outcomes between the EP and NF stent-assist coiling systems so as to comment on the safety, efficacy, complications, and recurrence rate of stent-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…In one case (5.9%) the stent did not open completely proximally, but this feature is also observed for other well-known brain stents and can be corrected in most clinical cases [3,[11][12][13][22][23][24]. The incidence of technical and clinical complications is similar to other braided stents [3,[22][23][24][25]. No procedure-related stroke occurred in our series, but this observation may be ascribed to the patient group being relatively small.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In one case (5.9%) the stent did not open completely proximally, but this feature is also observed for other well-known brain stents and can be corrected in most clinical cases [3,[11][12][13][22][23][24]. The incidence of technical and clinical complications is similar to other braided stents [3,[22][23][24][25]. No procedure-related stroke occurred in our series, but this observation may be ascribed to the patient group being relatively small.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, we recommend the jailing technique with the Accero stents. In one case (5.9%) the stent did not open completely proximally, but this feature is also observed for other well-known brain stents and can be corrected in most clinical cases [3,[11][12][13][22][23][24]. The incidence of technical and clinical complications is similar to other braided stents [3,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Another study of EP-stent assisted coiling by Mocco et al [ 16 ] reported a 3% rate of stent-related stenosis or occlusion. A meta-analysis of 1007 aneurysms in 915 patients treated with the EP stent reported incidences of thrombotic events and intraoperative rupture of 4.9% and 1.2%, respectively, with satisfactory embolization results in 85.45% of aneurysms [ 5 ]. In our study, 93.7% of aneurysms were finally completely or nearly completely embolized, which was better than the results reported in the abovementioned previous studies, indicating that the modified structure made the EP2 stent superior to the EP stent.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Recent studies have shown that the recanalization rate after embolization is lower with Neuroform Atlas than with Enterprise in stent-assisted coil embolization. 11,12 We therefore deployed a Neuroform Atlas at the initial treatment and performed coil embolization with a trans-cell approach.…”
Section: Discussionmentioning
confidence: 99%